Evaluation of Age-Dependent Immune Signatures in Patients With Multiple Sclerosis. Issue 6 (November 2021) - Eschborn, Melanie; Pawlitzki, Marc; Wirth, Timo; Nelke, Christopher; Pfeuffer, Steffen; Schulte-Mecklenbeck, Andreas; Lohmann, Lisa; Rolfes, Leoni; Pape, Katrin; Eveslage, Maria; Bittner, Stefan; Gross, Catharina C.; et al.
Abstract : Background and Objectives: In MS, an age-related decline in disease activity and a decreased efficacy of disease-modifying treatment have been linked to immunosenescence, a state of cellular dysfunction associated with chronic inflammation. Methods: To evaluate age-related immunologic alterations in MS, we compared immune signatures in peripheral blood (PB) and CSF by flow cytometry in patients with relapsing-remitting (RR) (PB n = 38; CSF n = 51) and primary progressive (PP) MS (PB n = 40; CSF n = 36) and respective controls (PB n = 40; CSF n = 85). Results: Analysis revealed significant age-related changes in blood immune cell composition, especially in the CD8 T-cell compartment of healthy donors (HDs) and patients with MS. However, HDs displayed a strong age-dependent decline in the expression of the immunoregulatory molecules KLRG1, LAG3, and CTLA-4 on memory CD8 T cells, whereas this age-dependent reduction was completely abrogated in patients with MS. An age-dependent increase in the expression of the costimulatory molecule CD226 on memory CD8 T cells was absent in patients with MS. CD226 expression correlated with disability in younger (⩽50 years) patients with MS. CSF analysis revealed a significant age-dependent decline in various immune cell populations in PPMS but not RRMS, suggesting a differential effect of aging on the intrathecal compartment in PPMS. Discussion: Our data illustrate that aging in MS is associated with a dysbalance between costimulatory and immunoregulatory signals provided by CD8 T cells favoring a proinflammatory phenotype and, more importantly, a pattern of premature immune aging in the CD8 T-cell compartment of young patients with MS with potential implications for disease severity.